Leptospirosis in pregnancy: a systematic review - Selvarajah, S; Ran, S; Roberts,, NW; Nair, M (Public Library of Science, 2021)
Introduction Leptospirosis is a leading zoonotic disease worldwide with more than 1 million cases in the general population per year. With leptospirosis being an emerging infectious disease and as the world’s environment changes with more floods and environmental disasters, the burden of leptospirosis is expected to increase. The objectives of the systematic review were to explore how leptospirosis affects pregnancy, its burden in this population, its effects on maternal and fetal outcomes and the evidence base surrounding treatment options. Methods We performed a systematic review of published and unpublished literature using automated and manual methods to screen nine electronic databases since inception, with no language restriction. Two reviewers independently screened articles, completed the data extraction and assessment of risk of bias. Due to significant heterogeneity and paucity of data, we were unable to carry out a meta-analysis, but we conducted a pooled analysis of individual patient data from the case reports and case series to examine the patient and disease characteristics, diagnostic methods, differential diagnoses, antibiotic treatments, and outcomes of leptospirosis in pregnancy. The protocol for this review was registered on the International Prospective Register of Systematic Reviews, PROSPERO: CRD42020151501. Results We identified 419 records, of which we included eight observational studies, 21 case reports, three case series and identified four relevant ongoing studies. Overall the studies were with moderate bias and of ‘fair’ quality. We estimated the incidence of leptospirosis in pregnancy to be 1.3 per 10,000 in women presenting with fever or with jaundice, but this is likely to be higher in endemic areas. Adverse fetal outcomes were found to be more common in pregnant patients who presented in the second trimester compared with patients who presented in the third trimester. There is overlap between how leptospirosis presents in pregnancy and in the general population. There is also overlap between the signs, symptoms and biochemical disturbances associated with leptospirosis in pregnancy and the presentation of pregnancy associated conditions, such as Pre-Eclampsia (PET), Acute Fatty Liver of Pregnancy (AFLP) and HELLP Syndrome (Haemolysis Elevated Liver enzymes Low Platelets). In 94% of identified cases with available data, there was an indicator in the patient history regarding exposure that could have helped include leptospirosis in the clinician’s differential diagnosis. We also identified a range of suitable antibiotic therapies for treating leptospirosis in pregnancy, most commonly used were penicillins. Conclusion This is the first systematic review of leptospirosis in pregnancy and it clearly shows the need to improve early diagnosis and treatment by asking early, treating early, and reporting well. Ask early—broaden differential diagnoses and ask early for potential leptospirosis exposures and risk factors. Treat early—increase index of suspicion in pregnant patients with fever in endemic areas and combine with rapid field diagnosis and early treatment. Report well—need for more good quality epidemiological studies on leptospirosis in pregnancy and better quality reporting of cases in literature.